Annotated typescript notes with commentary on the poems and arrangement of 'The golden joy' - MacDonagh, Thomas, 1878-1916 (1904)
MacDonagh writes "These commentaries are only by way of rough drafts. In them now there may be things written which are unnecessary in comment; and, on the other hand, it may be worth while (if commentary at all be worth while) to make them complete: here only some leading strands of thought in the more philosophic poems, and some references in others, are taken up, tenatively. The symbolism and imagery of the poems are not quite the same as those of any other poet and may for this demand commentary."
Keywords: MacDonagh, Thomas, -- 1878-1916 -- Poetic works; MacDonagh, Thomas -- 1878-1916; English poetry -- Irish authors -- 20th century; English literature -- Irish authors -- 20th century; Ireland -- History -- 1901-1910